(untitled) (Argos, 2017)
This paper is the second part of a study on two problems of Ancient Greek prosody, regarding the relation between the tonal accent of the language and the syllabic structure of words. In it, after a general introduction and a brief sum up of the first part, the problem of words with baritone accent on closed syllable is analyzed. The main novelty of the analysis is that the corpus used is the Homeric poetry, until today unattended as a source of evidence for Greek accent.